Structural determinants of tailored behavioral health services for sexual and gender minorities in the United States, 2010 to 2020: a panel analysis - Cory J. Cascalheira; Emily C. Helminen; Thomas J. Shaw; Jillian R. Scheer (BMC, 2022)
Abstract Background Research indicates that tailored programming for sexual and gender minority (SGM; e.g., lesbian, gay, bisexual, transgender, queer) people, compared to non-tailored programming, is effective for reducing the disproportionate health burden SGM people experience relative to the general population. However, the availability of SGM-tailored programming is often over-reported and inconsistent across behavioral health (i.e., substance use and mental health) facilities in the United States (U.S.). Methods Using panel analysis, the National Survey of Substance Abuse Treatment Services (N-SSATS), and the National Mental Health Services Survey (N-MHSS), this study examines structural stigma and government funding as two structural determinants affecting the availability of SGM-tailored programming in the U.S. Results Results indicated that from 2010 to 2020, reductions in structural stigma (i.e., increases in state-level supportive SGM policies) were positively associated with increases in the proportion of substance use treatment facilities offering SGM-tailored programming. This effect was significant after controlling for over-reporting of SGM-tailored programming and time- and state-specific heterogeneity. On average, the effect of reduced structural stigma resulted in approximately two new SGM-tailored programs in the short term and about 31 new SGM-tailored programs in the long term across U.S. substance use treatment facilities. Structural stigma did not predict the availability of SGM-tailored programming in mental health treatment facilities. Government funding was not significant in either data set. However, without correcting for over-reporting, government funding became a significant predictor of the availability of SGM-tailored programming at substance use treatment facilities. Conclusions Because SGM-tailored programming facilitates access to healthcare and the current study found longitudinal associations between structural stigma and the availability of SGM-tailored programming in substance use treatment facilities, our findings support claims that reducing structural stigma increases access to behavioral health treatment specifically and healthcare generally among SGM people. This study's findings also indicate the importance of correcting for over-reporting of SGM-tailored programming, raising concerns about how respondents perceive the N-SSATS and N-MHSS questions about SGM-tailored programming. Implications for future research using the N-SSATS and N-MHSS data and for public health policy are discussed.